Early pliocene fishes (Chondrichthyes, Osteichthyes) from Gran Canaria and Fuerteventura (Canary Islands, Spain) - Betancort-Lozano, Juan Francisco; Lomoschitz, Alejandro; Meco, J. (Estudios Geológicos, 2017)
Fossil fish teeth are contained in marine deposits dated at ca 4.8 Ma found on the islands of Gran Canaria and Fuerteventura (Canary Islands, Spain). These islands, situated in the North Atlantic Subtropical Gyre, can be con-sidered a mid-way stopover point between the Caribbean Sea, with the Central American Seaway about to close in this epoch, and the Mediterranean, in the first stage of its post-Messinian Gibraltar Seaway period. Accordingly, there existed extensive pantropical communication, particularly for nektonic animals capable of travelling large dis-tances. Los dientes fósiles de peces están contenidos en depósitos marinos datados en ca 4.8 Ma de las Islas de Gran Canaria y Fuerteventura (Islas Canarias, España). Estas islas, situadas en el Giro subtropical del Atlántico Norte, pueden considerarse una estación intermedia entre un Mar Caribe que estaba cercano al cierre del Paso de América Central, y el Mediterráneo en su primera etapa tras la apertura post-Mesiniense de Gibraltar. Ello permitía una comunicación pantropical para los animales del necton que eran capaces de desplazarse a grandes distan-cias. Se identifican por primera vez los peces Chondrichthyes Carcharocles megalodon, Parotodus benedeni, Cosmopolitodus hastalis, Isurus oxyrinchus, Carcharias cf. acutissima, Carcharhinus cf. leucas, Carcharhinus cf. priscus, Galeocerdo cf. aduncus y las species de Osteichthyes Archosargus cinctus, Labrodon pavimentatum